2022
DOI: 10.3389/fphar.2022.899725
|View full text |Cite
|
Sign up to set email alerts
|

A KRAS-Associated Signature for Prognostic, Immune and Chemical Anti-Cancer Drug-Response Prediction in Colon Cancer

Abstract: Background: KRAS mutation, one of the most important biological processes in colorectal cancer, leads to poor prognosis in patients. Although studies on KRAS have concentrated for a long time, there are currently no ideal drugs against KRAS mutations.Methods: Different expression analysis and weighted gene coexpression network analysis was conducted to select candidate genes. Log-rank tests and Cox regression picked out the prognostic genes to build a KRAS-related gene prognostic score (KRGPS). A nomogram base… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 33 publications
0
1
0
Order By: Relevance
“…NK cells play important roles in immune surveillance and can directly kill tumor cells via perforin and granzyme release [ 37 , 38 ]. There is increasing evidence that the numbers of infiltrating NK cells in tumor tissues are positively correlated with tumor patient survival [ 39 42 ]. Consistent with previous research, from TCGA data analysis we found that activated NK cell levels are decreased and resting NK cell levels are increased in CRC tissues, suggesting an altered proportion of NK cell subsets.…”
Section: Discussionmentioning
confidence: 99%
“…NK cells play important roles in immune surveillance and can directly kill tumor cells via perforin and granzyme release [ 37 , 38 ]. There is increasing evidence that the numbers of infiltrating NK cells in tumor tissues are positively correlated with tumor patient survival [ 39 42 ]. Consistent with previous research, from TCGA data analysis we found that activated NK cell levels are decreased and resting NK cell levels are increased in CRC tissues, suggesting an altered proportion of NK cell subsets.…”
Section: Discussionmentioning
confidence: 99%